Student’s Learning Outcomes in Online Fun Learning using Video at SMP Wahidiyah Kediri - Jenny Ika Misela; Mahendra Puji Permana Aji, Mahendra Puji Permana Aji (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The pandemic has changed the way of teacher delivering material to the students. SMP Wahidiyah Kediri has supported the online learning for its students in order to bring new learning experience to the students and also in order to make the teaching learning process better in this new pandemic era. English as one of the compulsory subject at Junior High would also use online learning as media in teaching learning process. The online learning should make the students gain the knowledge better but also in a fun way. Video is used as one of the media in teaching English as it is bring joy and fun to the students. The study involved the seventh grade students of SMP Wahidiyah Kediri. It was completed in eight meetings. The researcher used quantitative method with t-tests to analyze the data. The result showed that there were significantly different levels of learning outcomes between the students who were taught by online fun video learning with the students who were not. The data showed that t-test > t-table (3807 > 1993) so that Ha is accepted and Ho is rejected. The average score showed that the class control has lower value than the class experiment. So it can be concluded that online fun video learning could improve the students’ learning outcome